Complex TE-modes in Slotted Waveguides of Arbitrary Cross Section - Topal, Turker; Vinogradova, Elena; Tuchkin, Yury A. (IEEE, 2021)
Implementation of the rigorous Analytical Regularization Method is presented for plane wave scattering by arbitrary two-dimensional cavities with longitudinal slit. The general solution of the Neumann boundary value problem for Helmholtz equation is obtained in a form of two coupled infinite systems of linear algebraic equations of the second kind. Compactness of the matrix operator provides efficient numerical solution of the joint system by truncation method. Fast convergence of the truncated system of linear algebraic equations makes this method an effective instrument for accurate analysis of spectral and diffraction problems. Considering the homogeneous version of equations and finding the complex roots of their determinants, we calculate the complex eigenvalues of complex oscillations. Employing spline interpolation and mollifier function the problem geometry is generalized.
International Symposium of the Applied-Computational-Electromagnetics-Society (ACES) -- AUG 01-05, 2021 -- ELECTR NETWORK
Keywords: 2D slotted cavities; Analytical Regularization Method; complex eigenvalues; Helmholtz equation; Neumann problem